Introducing Wayang Art through Puppet-Making and Coloring Activities for MI Al-Islam Kepundungan Students - Carrisa Adisvia Finansa; Mujiyono Mujiyono (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
This study aims to examine the learning activities of introducing the art of puppetry to grade IV students of MI Al-Islam Kepundung through the activity of making and coloring puppets. The learning activity was carried out to increase students' understanding of traditional cultural arts, especially puppetry as Indonesia's cultural heritage. The method used is a descriptive qualitative approach. The subjects of the study are IV students and teachers. This research highlights the learning process and the work of students. Data was obtained through observation, brief interviews, documentation, and then processed through reduction, presentation, and drawing conclusions to describe the course of learning and student creativity. With the stages, the teacher gave an introduction to the puppet character of the Pandawa Lima, and gave an explanation of the cultural values it contains. The results of the study show two learning processes, namely cultural introduction through stories and interactive dialogues, and the realization of students' creativity through real works. The teacher introduced the Pandawa Lima puppet shop and explained the cultural values it contains, then the activity continued with students starting to design puppet sketches according to their own imaginations, then coloring them freely. These two processes complement each other in producing a meaningful and immersive learning experience. The result of children's works is a unique, colorful, imaginative, symbolic, and entertaining creative way. In conclusion, the approach of introducing puppet art through making and coloring activities has proven to be effective in increasing creativity, understanding, and fostering students' love for local culture. This approach can be used as an alternative learning strategy in efforts to preserve traditional arts in elementary schools.